2020
DOI: 10.1021/acs.jpcc.0c00273
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Decomposition Characteristics and Thermal Safety of Dihydroxylammonium 5,5′-Bistetrazole-1,1′-diolate Based on Microcalorimetric Experiment and Decoupling Method

Abstract: A microcalorimeter (C600) was used to conduct dynamic heating experiments on dihydroxylammonium 5,5′-bistetrazole-1,1′-diolate (TKX-50), and the results were compared with those of differential scanning calorimetry (DSC). The effect of mass scale on the thermal decomposition characteristics of TKX-50 was also analyzed. The thermal decomposition curves were decoupled by mathematical method, and the kinetic parameters of each step were obtained. The thermal decomposition characteristics of TKX-50 were further an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…[17][18][19][20][21][22][23] Among the most promising molecules developed with the aim of replacing RDX are the bis-hydroxylammonium derivatives of 3,3 0 -dinitro-bis-1,2,4-triazol-1,1 0 -diolate (MAD-X1) 19 and 5,5 0bistetrazol-1,1 0 -diolate (TKX-50), 18 which are attracting great attention in the international community. [24][25][26][27][28][29][30] Combination of 1-hydroxy-tetrazole and 1-hydroxy-3-nitro-1,2,4-triazole yields the hybrid molecule 1-hydroxy-3-nitro-(1,2,4-triazol-5-yl)-1-hydroxy-tetrazole (1) with the aim to combine the positive properties of the fundamental symmetric bis-heterocycles in a new asymmetric molecule: preferrable the high heat of formation of 1,1 0 -dihydroxy-5,5 0 -bistetrazole (A) with the high density and insensitivity toward external stimuli of 1,1 0 -dihydroxy-3,3 0 -dinitro-bis-1,2,4-triazole (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20][21][22][23] Among the most promising molecules developed with the aim of replacing RDX are the bis-hydroxylammonium derivatives of 3,3 0 -dinitro-bis-1,2,4-triazol-1,1 0 -diolate (MAD-X1) 19 and 5,5 0bistetrazol-1,1 0 -diolate (TKX-50), 18 which are attracting great attention in the international community. [24][25][26][27][28][29][30] Combination of 1-hydroxy-tetrazole and 1-hydroxy-3-nitro-1,2,4-triazole yields the hybrid molecule 1-hydroxy-3-nitro-(1,2,4-triazol-5-yl)-1-hydroxy-tetrazole (1) with the aim to combine the positive properties of the fundamental symmetric bis-heterocycles in a new asymmetric molecule: preferrable the high heat of formation of 1,1 0 -dihydroxy-5,5 0 -bistetrazole (A) with the high density and insensitivity toward external stimuli of 1,1 0 -dihydroxy-3,3 0 -dinitro-bis-1,2,4-triazole (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…17–23 Among the most promising molecules developed with the aim of replacing RDX are the bis-hydroxylammonium derivatives of 3,3′-dinitro-bis-1,2,4-triazol-1,1′-diolate (MAD-X1) 19 and 5,5′-bistetrazol-1,1′-diolate (TKX-50), 18 which are attracting great attention in the international community. 24–30…”
Section: Introductionmentioning
confidence: 99%
“…Kinetic modeling of heterogeneous reactions that occur in thermal decomposition of energetic materials (EM) is of paramount importance for understanding their thermal behavior in deep and for the thermal safety assessment. At present, the methodology for kinetic modeling has been developed mainly based on the assumption of single-step reactions. However, in many EM cases, the actual kinetic behaviors are quite complicated that cannot be correctly described by simple reaction assumptions. In particular, when multistep (or multiple) heterogeneous reactions occur simultaneously, it is a challenging task to explicate the overall heterogeneous process and to clarify the detailed process of each reaction step by analyzing experimental calorimetric data from thermal analysis technology.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high mechanical sensitivity of HMX, in order to improve its safety, HMX was often mixed with many cladding materials to promote the safety of explosives, and has been widely used in the field of mixed explosives or propellants. The literatures [19–27] explored the effects of RDX, TNT, aluminized hydrides, TKX–50, CL‐20 and other substances on the thermal safety, isothermal kinetics, explosion performance, thermal decomposition mechanism, sensitivity and mechanical properties of HMX. It was found that the properties of HMX alteration significantly in their mixtures.…”
Section: Introductionmentioning
confidence: 99%